Revitalisasi Peradaban Islam: Menjembatani Teori Reformis dan Realitas Kontemporer - Ahmad Khaerussalam; Ahmad Faruq Khaqiqi; Abdurrahman Siregar (GHAITSA : Islamic Education Journal, 2025)
This study explores the efforts to revive Islamic civilization through the ideas of modern reformist thinkers such as Jamaluddin al-Afghani, Muhammad Abduh, Rasyid Ridha, Fazlur Rahman, Syed Naquib al-Attas, Ismail Raji al-Faruqi, and Nurcholish Madjid. Their thoughts span various domains, including politics, education, and Islamic epistemology. However, the implementation of these theories in the contemporary Muslim world still faces numerous obstacles, including structural challenges, global pressures, and internal issues within the Muslim community. This study employs a qualitative approach using literature review methods to analyze these barriers and offer potential solutions. The findings suggest that the revival of Islamic civilization must begin with educational reform, the strengthening of critical thinking culture, and collaboration among Muslim nations in confronting global challenges collectively.